In a perfect ocean : the state of fisheries and ecosystems in the North Atlantic Ocean - Pauly, D. (Daniel) (State of the world's oceans series., 2003)
In a Perfect Ocean is the first in a series of assessments of the world's marine ecosystems. In this first comprehensive, empirical portrait of the North Atlantic, the authors use traditional catch data and cutting-edge scientific techniques to provide an indisputable picture of an ocean whose food webs have been dramatically altered. They then explain how the North Atlantic arrived at this state, and how we can return it to health.